2007
DOI: 10.1007/s10706-007-9126-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of Richards equation in partially saturated porous media: under-relaxation and mass balance

Abstract: Numerical simulation of Richards equation in unsaturated soil is known to be difficult because of the highly non-linear material properties involved. An extensive study was conducted to clarify the role of mass balance and under-relaxation on the rate in which the correct solution is approached. Both finite element and finite difference techniques were considered. For the former, the hbased formulation was compared with a massconservative mixed form. The conductivity function (K) was under-relaxed in two ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…The porous media hydraulic properties, initial and boundary conditions for this validation test are shown in table 4. Figure 3 provides the comparison of the results obtained from present flow model with that of Phoon et al (2007). It is observed that the model predictions are in good agreement with the reported values of pressure head.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The porous media hydraulic properties, initial and boundary conditions for this validation test are shown in table 4. Figure 3 provides the comparison of the results obtained from present flow model with that of Phoon et al (2007). It is observed that the model predictions are in good agreement with the reported values of pressure head.…”
Section: Resultssupporting
confidence: 66%
“…To examine the performance of the flow model (equation 1), numerical simulations were carried out using data from the one-dimensional numerical experiment of Phoon et al (2007), where water infiltrates into a homogeneous soil column which is initially dry. The porous media hydraulic properties, initial and boundary conditions for this validation test are shown in table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Since the analytical solutions are not available for the present study, the numerical model has been validated separately for water flow in unsaturated zone and bioclogging in saturated zone with their appropriate published analytical/numerical solution. The numerical solution for water flow in an unsaturated zone has been provided by Mitchell and Mayer (1998), Lehmann and Ackerer (1998) and Phoon et al (2007). It is observed from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Para validar o código computacional foram resolvidos alguns problemas clássicos da literatura, a saber: Haverkamp et al [11], Phoon et al [7], Vasconcellos [2], Celia et al [8] e Juncu et al [5]. Igualmente foram utilizadas as soluções semi-analíticas de Philip [6], Warrick's et al…”
Section: Validação Do Código Computacionalunclassified